Ginsenoside Rb3 attenuates oxidative stress and preserves endothelial function in renal arteries from hypertensive rats. (July 2014) - Wang, Youhua; Dong, Jinghui; Liu, Ping; Lau, Chi Wai; Gao, Zhen; Zhou, Duan; Tang, Jingyi; Ng, Chi Fai; Huang, Yu
<x xml:space="preserve">Abstract</x> Background and Purpose P anax ginseng is commonly used to treat cardiovascular conditions in Oriental countries. This study investigated the mechanisms underlying the vascular benefits of ginsenoside Rb3 (Rb3) in hypertension. Experimental Approach Rings of renal arteries were prepared from spontaneously hypertensive rats (SHRs) and normotensive Wistar‐Kyoto (WKY) rats and were cultured ex vivo for 8 h. Contractile responses of the rings were assessed with myograph techniques. Expression of NADPH oxidases was assessed by Western blotting and immunohistochemistry. Reactive oxygen species (ROS) were measured using dihydroethidium fluorescence imaging and production of NO was determined using the fluorescent NO indicator DAF‐FM diacetate in human umbilical vein endothelial cells. Key Results E x vivo treatment with Rb3 concentration‐dependently augmented endothelium‐dependent relaxations, suppressed endothelium‐dependent contractions and reduced ROS production and expressions of NOX‐2, NOX‐4 and p67phox in arterial rings from SHR. Rb3 treatment also normalized angiotensin II (Ang II)‐stimulated elevation in ROS and expression of NOX‐2 and NOX‐4 in arterial rings from WKY rats. Rb3 inhibited Ang II‐induced reduction of NO production and phosphorylation of endothelial NOS in cultures of human umbilical vein endothelial cells. Rb3 also inhibited oxidative stress in renal arterial rings from hypertensive patients or in Ang II‐treated arterial rings from normotensive subjects. Conclusion and Implications Ex vivo Rb3 treatment restored impaired endothelial function in arterial rings from hypertensives by reversing over‐expression of NADPH oxidases and over‐production of ROS, and improved NO bioavailability. Our findings suggest that medicinal plants containing Rb3 could decrease oxidative stress and protect endothelial function in hypertension.